Suppressive effects of tenofovir disoproxil fumarate, an antiretroviral prodrug, on mineralization and type II and type III sodium‐dependent phosphate transporters expression in primary human osteoblasts. Issue 6 (7th March 2018) - Barbieri, Anna Maria; Chiodini, Iacopo; Ragni, Enrico; Colaianni, Graziana; Gadda, Franco; Locatelli, Marco; Lampertico, Pietro; Spada, Anna; Eller‐Vainicher, Cristina
Abstract: Tenofovir disoproxil fumarate (TDF) is an antiretroviral drug commonly used for the management of Human Immunodeficiency Virus (HIV) in highly active antiretroviral therapy (HAART) and of chronic Hepatitis B Virus (HBV) infections. Long‐term TDF‐treated subjects present decrease of bone mineral density and rarely severe osteomalacia. Although these adverse effects have been attributed to the impaired proximal tubule function, a possible direct involvement of TDF on osteoblasts should be taken into account. The aim of this study was to evaluate whether sodium phosphate transporters NPT2A (sodium‐dependent phosphate transport protein 2A), NPT2C (sodium‐dependent phosphate transport protein 2C), PIT1 (sodium‐dependent phosphate transporter 1), and PIT2 (sodium‐dependent phosphate transporter 2) were expressed in primary human osteoblasts (HOBs), whether their expression was related to HOBs differentiation and whether TDF could affect mineralization and gene expression. PIT1 and PIT2 were expressed under proliferating conditions and increased after induction of mineralization, while NPT2A and NPT2C were almost undetectable. In HOBs TDF exposure induced a significant dose‐dependent decrease in mineralization. Moreover, TDF caused a reduction of COL1A1 and of ATF4 expression in differentiated HOBs. In summary, HOBs do not express NPT2A and NPT2C and do express PIT1 and PIT2, suggesting a role of these two latter in human osteoblast mineralization. TDF impairs osteoblast mineralization, confirming a direct negative effect on bone. Therefore, in clinical practice, bone damage must be suspected and evaluated also in patients receiving TDF without kidney function alterations. Abstract : The expression of sodium phosphate transporters NPT2A, NPT2C, PIT1, and PIT2 was analyzed in primary human osteoblasts (HOBs). The antiretroviral tenofovir induced a significant dose‐dependent decrease in mineralization in HOBs and altered the expression of late differentiation osteoblast markers.